Health policy and genetic endowments: Understanding sources of response to Minimum Legal Drinking Age laws. (3rd November 2020) - Fletcher, Jason M.; Lu, Qiongshi
Abstract: This paper uses policy‐induced variation in legal access to alcohol in the United States to explore interactions between genetic predispositions and health behaviors. It is well known that Minimum Legal Drinking Age (MLDA) laws have discrete impacts on binge drinking behaviors, but less is known about heterogeneity of the effects and the characteristics of individuals most and least affected. Using the Add Health data, this paper explores differential policy effects based on polygenic scores (PGS), which are genome‐wide summary measures predicting health outcomes. Specifically, we leverage PGS for alcoholism and for a broader set of risk‐taking behaviors to explore heterogeneities in response to the policy and consider mechanisms for the responses. Like previous literature using the Add Health and other datasets, we find main effects of MLDA in increasing recent binge drinking episodes by approximately 5 percentage points. We find MLDA effects are concentrated entirely in individuals with high PGS for alcohol use. We are also able to compare these results with measures of parental alcoholism as a global proxy for family history.